2010
DOI: 10.1515/znc-2010-7-814
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression Analysis of 1 L-myo-Inositol-1-phosphate Synthase Gene from Ricinus communis L.

Abstract: A novel 1 L-myo-inositol-1-phosphate synthase (MIPS, EC 5.5.1.4) gene, designate rcMIPS, was cloned from Ricinus communis. It contained an open reading frame (ORF) of 1669 bp coding for a peptide of 510 amino acids with a molecular mass of 56 kDa. Sequence anaylsis showed high homology compared to other plant MIPS genes, because it contained typical domains owned by MIPS enzymes. The transcript levels of the rcMIPS gene in leaves, stems, and roots were examined after drought stress for 24, 48, and 72 h. The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In this study, in leaves of drought-resistant strain FS43 and sensitive strain FS38, MIPS were up-regulated following water deficit (Tab.1). This result is in concordance with a previous study, which indicated that MIPS plays an important role in drought-resistance (Wei, W. et al, 2010). …”
supporting
confidence: 94%
“…In this study, in leaves of drought-resistant strain FS43 and sensitive strain FS38, MIPS were up-regulated following water deficit (Tab.1). This result is in concordance with a previous study, which indicated that MIPS plays an important role in drought-resistance (Wei, W. et al, 2010). …”
supporting
confidence: 94%
“…India, Brazil and China are the major oil crop producers in the world and, recently, biodiesel production has received wide attention in Brazil, where the Program for Production and Use of Biodiesel (PNPB) has identified castor bean as the ideal species for oil production which, in addition, could help to promote social development in the semi-arid regions of Brazil (Cesar and Batalha, 2010). Its agronomic importance stimulated molecular research in R. communis related to seed maturation (Cagliari et al , 2010; Sánchez-García et al , 2010; Loss-Morais et al , 2013), plant development (O'Leary et al , 2011), and responses to biotic and abiotic stresses (Wei et al , 2010; Maciel et al , 2011). Characterization and expression profiles of several genes from R. communis have been reported (Cagliari et al , 2010; Chileh et al , 2010; Wei et al , 2010; Maciel et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Its agronomic importance stimulated molecular research in R. communis related to seed maturation (Cagliari et al , 2010; Sánchez-García et al , 2010; Loss-Morais et al , 2013), plant development (O'Leary et al , 2011), and responses to biotic and abiotic stresses (Wei et al , 2010; Maciel et al , 2011). Characterization and expression profiles of several genes from R. communis have been reported (Cagliari et al , 2010; Chileh et al , 2010; Wei et al , 2010; Maciel et al , 2011). In this study we focus on seed germination and seedling growth, since a better understanding of the biochemical and molecular aspects of these processes in R. communis is crucial for the breeding of high-yielding varieties adapted to various growing environments (Severino and Auld, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…WLR measurements using detached leaves were already applied to characterize drought tolerance in crops like wheat, maize, wild barley and sunflower (Rampino et al 2006;Clarke and McCaig 1982;Ristic and Jenks 2002;Suprunova et al 2004;Teulat et al 2003). RWC was a relevant screening tool for drought tolerance in cereals (Teulat et al 2003;Muthurajan et al 2010) and castor bean (Ricinus communis L.) (Wei et al 2010). Characterization of our genotypes by leaf WLR and RWC after 4h confirms that F. chiloensis is drought tolerant.…”
Section: Discussionmentioning
confidence: 63%